Privatisations and institutions: A cross-country analysis - Bernardo Bortolotti; Marcella Fantini; Domenico Siniscalco; Serena Vitalini (Fondazione Eni Enrico Mattei (FEEM), 1997)
What legal, political and economic institutions are shaping privatisations processes in the world? This paper addresses the issue presenting new evidence for a sample of 49 countries. From an empirical analysis for the period 1977-1996, the decision to privatise appears to be related to political preferences and macroeconomic conditions, but the success of a privatisation process requires, in addition, appropriate legal institutions and developed capital markets.
Keywords: G30; K22; 330; Privatisations; Corporate law; Capital markets; Privatisierung; Institutionalismus; Finanzmarkt; Schätzung; Welt